Diversity in Synthesis of N-Heterocycles from Simple Propargylic Alcohols - Gayon, Eric; Gerard, Hélène; Vrancken, Emmanuel; Campagne, Jean-Marc (Synlett, 2015)
In this account, we summarize our recent work on the preparation of various N-heterocycles, starting from propargylic alcohols. Our aim was to develop versatile and selective one-pot procedures that would permit the synthesis of large collections of heterocycles, such as di- or tri-substituted isoxazolines and isoxazoles, cis-aziridines, and pyrimidines, by fine changes in the reaction conditions. When needed, mechanistic studies have been performed by combining experimental work with density functional theory calculations.1 Introduction2 Synthesis of Disubstituted Isoxazolines3 Synthesis of Disubstituted Isoxazoles4 Synthesis of cis-Acylaziridines5 Trisubstituted Isoxazolines and Isoxazoles6 β-Enaminones and Pyrimidines7 Conclusion
Keywords: iron; palladium; heterocycles; isomerization; ring closure; catalysis